FROM MYTHOLOGY TO MODERNITY: THE TRANSFORMATION OF TRADITIONAL INDONESIAN SUPERHEROES IN THE DIGITAL AGE - Saptanto, Deswandito Dwi; Nurhamidah, Idha; Hardiany , Dewi Rosnita (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2024)
The transformation of traditional Indonesian superheroes such as Gundala, Si Buta dari Gua Hantu, Maza, Nusantara and Godam in the digital era, showing how traditional elements can be adapted to modern media. These Indonesian superheroes not only symbolise cultural heritage, but also reflect the aspirations and struggles of Indonesians at various times. In contrast, American superheroes such as Superman, Batman and Spider-Man dominate the global popular culture landscape and represent modern values such as individualism, capitalism and universal heroism. This study also discusses the role of superheroes in expressing the values and identities of their creators, as well as the impact of the dominance of American superhero culture on the global cultural market and its pressure to adapt established visual and narrative standards. It has been found that recent superhero works are more inclusive and reflect the diversity and intimacy of society more broadly. This article highlights the importance of integrating traditional values and cultural heritage with the evolving context of the digital age.